Resonant Dissidents: graffiti in political demonstrations - Souza, Penha de Fátima da Cruz de; França, Claudia (Farol, 2024)
In this article, we present a study on the use of graffiti in political demonstrations. To this end, we highlight some historical moments that are considered fundamental to mention when dealing with this topic; these are moments in which graffiti artists opposed political-behavioral hegemony and took action, using graffiti as a tool for social struggle. We will also point out more recent movements that took place in Brazil and especially in Vitória-ES.